Measurements and linearized models for golf ball bounce on a green - Biber, S. W.; Jones, K. M.; Champneys, A. R.; Green, R.; Szalai, R. (Sports Engineering, 2023)
A detailed set of experiments are described that capture over a 1000 different instances of the bounce of a golf ball on a green. Video analysis was used to capture ball`s velocity and spin just before and after each bounce for a wide variety of landing conditions. Data are presented from two different turfs; one artificial and one from a typical tee. Measurement errors and repeatability are analysed. The data are compared to predictions from models of rigid bounce with friction, including Penner`s modification to account for elasto-plasticity. Coefficients of restitution and friction, and Penner`s effective contact angle are fit from the data. A better fit to the data is found using a non-physical piecewise-affine landing to lift-off relationship, which distinguishes between cases that bounce in pure slip from those that undergo rolling. Nevertheless, even balls that undergo rolling are typically found to lift-off slipping, having undergone spin reversal. The findings suggest that further effort needs to be spent on finding simple physics-based models of golf ball bounce on a green.